2014
DOI: 10.18632/oncotarget.2691
|View full text |Cite
|
Sign up to set email alerts
|

Development and prospective multicenter evaluation of the long noncoding RNA MALAT-1 as a diagnostic urinary biomarker for prostate cancer

Abstract: The current strategy for diagnosing prostate cancer (PCa) is mainly based on the serum prostate-specific antigen (PSA) test. However, PSA has low specificity and has led to numerous unnecessary biopsies. We evaluated the effectiveness of urinary metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1), a long noncoding RNA, for predicting the risk of PCa before biopsy. The MALAT-1 score was tested in a discovery phase and a multi-center validation phase. The predictive power of the MALAT-1 score was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 30 publications
3
116
0
1
Order By: Relevance
“…More human specimens are needed to clarify whether DANCR can be used as diagnostic and prognostic marker of prostate cancer. Moreover, several lncRNAs, such as PCA3 and MALAT-1, can be used as diagnostic urinary biomarkers for prostate cancer [3536], thus DANCR expression in the urine of prostate cancer patients should be measured and analyzed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…More human specimens are needed to clarify whether DANCR can be used as diagnostic and prognostic marker of prostate cancer. Moreover, several lncRNAs, such as PCA3 and MALAT-1, can be used as diagnostic urinary biomarkers for prostate cancer [3536], thus DANCR expression in the urine of prostate cancer patients should be measured and analyzed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have demonstrated that lncRNAs play a very important role in tumor occurrence, invasion, and metastasis and can be considered as biomarkers in many human cancers [13][14][15]28]. Some previous studies have shown that many lncRNAs were upregulated or down-regulated dramatically in tumor tissues in contrast to non-tumor tissues [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Some lncRNAs can be detected in plasma of both healthy people and certain patients. LncRNAs have been reported as biomarkers for the diagnosis of multiple diseases [11,12], including cancers, such as cancers of colorectum, prostate and bladder [13][14][15]. Some previous studies showed that many lncRNAs were up-regulated or down-regulated significantly in tumor tissues compared with non-tumor tissues [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…MALAT1 was one of the first lncRNAs to be demonstrated its close implication in cancer, and a series of studies has established the importance of MALAT1 as a marker of cancers ( [95], multiple myeloma [73,96,97], neuroblastoma [37,38], osteosarcoma [42,98], ovarian cancer [99], pituitary adenoma [100], prostate cancer [101][102][103], and renal cell carcinoma [50,104].…”
Section: Malat1 and Cancermentioning
confidence: 99%